Recasting China’s Foreign Policy: Focusing on Post-Jiang Leaders’ Authority Building - Park, Hun Joo; Kim, Daria (KDI School of Public Policy and Management, 2020)
This article is structured as follows. Part II provides a succinct summary of recent China’s assertive external conduct. Based on the created Assertive Foreign Policy Index, we choose several cases from the sample for the deeper analysis to understand the reasons behind foreign policy decisions. Part III illuminates the authority-building theoretical framework, redefined from Breslauer (1982) analysis of post-Stalin leaders. Through the authority-building framework lens, we can penetrate into China’s domestic politics, having a better understanding of the decision-making process. Part IV explains the specific characteristics of leaders’ authority-building in post-Jiang’s China and its implications to foreign policy. Part V provides an in-depth case study analysis, comparing Hu and Xi authorities and its influence on a range of foreign policy choices they have. Part VI concludes the analysis and provides some insight for further research.